The Implementation Of Pitra Yadnya Ceremony In The Pandemic Covid-19 Time At The Hindu Community In Saksari Hamlet North Cakranegara Lombok - Gusti Ayu Santi Patni R. (Jurnal Penelitian Agama Hindu, 2021)
This research aims to conduct a study regarding the implementation of the pitra yadnya ceremony during the Covid-19 pandemic in the Saksari hamlet, North Cakranegara subdistrict, Lombok. The background of this research is related to the habits of Hindus in this area to carry out the pitra yadnya ceremony by continuing the tradition of menyama braya, saling rojong, sidikara, and fraternal ties in creating harmony. The pitra yadnya tradition carried out by Hindus today is experiencing adjustments as a result of the spread of the Covid 19 pandemic, with social restrictions. In this regard, this research focuses on three formulations of problems, namely (1) how is the pitra yadnya ceremony; (2) what is the family strategy in implementing the pitra yadnya ceremony; and (3) what are the implications of the pitra yadnya Ceremony for community during the Covid-19 Pandemic in the Saksari hamlet, North Cakranegara subdistrict? This study was designed in a qualitative descriptive study to provide an overview of the implementation of the pitra yadnya ceremony at the research location. Based on the research results found three findings. First, the pitra yadnya ceremony procedures during the Covid-19 pandemic were carried out simply, without reducing the meaning of the ceremony, according to the concepts of iksa, sakti, desa, kala, patra, and tattwa. Second, the family strategy in carrying out the pitra yadnya ceremony during the Covid-19 pandemic is to continue to carry out the ceremony by following the advice and appeals of the Parisadha Hindu Dharma Indonesia (PHDI) or Hindu religious council and health protocols. Third, the implication of the pitra yadnya ceremony for the community during the Covid-19 pandemic is the change in the social order of the community, such as menyama braya, saling rojong, and sidikara, from an economic point of view, it was much more efficient than the situation before the Covid-19 pandemic.